(untitled) (Entrepreneurship Journal for Finance and Business, 2022)
This study aims to demonstrate liquidity risk and its impact on banking security using the audited annual financial statements of Iraqi commercial banks for the period between 2016-2020AD for five of the Iraqi commercial banks. To test the study hypotheses, the percentages that represent the indicators of liquidity and banking security were extracted, and using the simple regression analysis method, the correlation coefficient, the coefficient of determination and the T-test as tools for analysis through the statistical program Mini tab 18, the results showed a statistically significant relationship between the dependent and independent variable represented by measures Bank liquidity and banking security in the Iraqi commercial banks, the subject of the study, and some conclusions and recommendations were reached for the purpose of overcoming the risks of bank liquidity.